The Integration and Interconnection of Sciences in Pesantren Tafsir: An Analysis of Tafsir Sūrah Yāsīn by KH Bisri Mustafa - Baidowi, Ahmad; Ma'rufah, Yuni; Roswantoro, Alim (QOF, 2024)
The history of the writing of Qur’anic tafsir in Indonesia is closely tied to the works of Ulama within the Pesantren. The development of Qur’anic tafsir writing in the Pesantren environment has been highly dynamic, characterized by variations in appearance, writing style, language, script, interpretative style, and approach. One distinctive feature of tafsir works produced within the Pesantren is exemplified by the Tafsir Sūrah Yāsīn, authored by KH Bisri Mustafa from Pesantren Raudlotut Thalibin Rembang, Central Java. This work showcases a unique interpretation, particularly in its approach to natural science verses. Adopting the integration model introduced by Ian G. Barbour, it can be argued that KH Bisri Mustafa’s interpretation of natural verses aligns with the category of natural theology. This perspective asserts that awareness of God can be discerned through natural phenomena, where the existence of God is reflected in the design of nature. The intricate design of nature fosters awareness of God’s presence and existence. This study employs a descriptive-analytical approach to examine KH Bisri Mustafa’s interpretation of scientific verses in surah Yāsīn. The findings contribute to the ongoing discourse on integrating religion and science, particularly within the context of Qur’anic tafsir in Pesantren circles.